Umbilical cord mesenchymal stem cells promote the repair of trochlear groove reconstruction in dogs - He, Shi; Zhang, Jun; Chen, Wojun; Yan, Yanyao; Lin, Yuhong; Zhang, Yicheng; Lei, Shirui; Huang, Chuyin; Chen, Shengfeng; Chen, Zhisheng; Liu, Canying; Bai, Yinshan; et al. (Frontiers in Veterinary Science, 2022)
Trochlear Groove Reconstruction (TGR) is the common treatment of patellar luxation (PL) in dogs. Nevertheless, the prognosis of TGR is poor due to the cartilage damage and secondary inflammation. To study the repair effect of canine umbilical cord mesenchymal stem cells (UC-MSCs) after TGR, 10 experimental dogs were performed TGR surgery and then randomized to two groups: Treatment group (1mL suspension allogeneic UC-MSCs（106 cells /kg）was injected into the cavum articulare on day 0, 7, and 14 after TGR); and the Model group (injected with 1mL of physiological saline as negative control). The therapeutic effect of UC-MSCs was studied by blood routine examination, inflammatory factor index detection, double-blind knee score, histopathology and computed tomography (CT) scans. The results showed that the total number of white blood cells and neutrophils in the model group were significantly higher than those in the treatment group in both 7 days and 21 days postoperatively (P＜0.05); there were no significant changes in the levels of IL-6, MMP-13, and TGF-β1 between the model group and the treatment group throughout the days of testing. The double-blind knee scores of the treatment group were significantly lower than the model group on the 1st , 4th and 5th days postoperatively (P＜0.05). The treatment group showed low pain sensation, stable gait and fast recovery of muscle strength in the knee score, and the wound healing of the treatment group returned to normal on the 5th day after surgery; CT scans and gross observation showed that the cartilage growth in the treatment group was faster than that in the model group. Histological observation of cases showed that fibro chondrocytes were predominantly found in the treatment group, and the distribution of chondrocytes was uneven, while the model group showed a large number of fibrous tissue hyperplasia, fissures and unequal matrix staining. Intra-articular injection of UC-MSCs after TGR has the effect of relieving pain and promoting the repair of bone defects, making the operative limb recover function earlier, making up for the deficiency of TGR and improving the effect of PL treatment.